Factors influencing the implementation of MSPO among organized smallholders at Felda Lepar Utara 03, Jerantut,Pahang / Ahmad Hafidz Ikhwanuddin Azman - Azman, Ahmad Hafidz Ikhwanuddin (Faculty of Plantation and Agrotechnology, 2019)
Oil palm industry plays a major role in contributing towards national economy. Lately, the implementation of Malaysian Sustainable Palm Oil (MSPO) was mandatory to all of the plantations in our country. The implementation of MSPO helps to maintain the sustainability of oil palm while preserving the wildlife habitat. The objective of this study is to determine the factors influencing the implementation of MSPO, to determine the relationship between the factors and the implementation of MSPO and to identify the most dominant factor that influences the implementation of MSPO towards organized smallholders. The method for this study was survey by using questionnaire. The study was conducted at Felda Lepar Utara 03 and the total numbers of respondents were 92. The data was analyzed by using Statistical Package for the Social Sciences (SPSS). Based on the data analysis, it can be determined all of the factors are positive and the samples were adequate. This can be explained from the value of Kaiser-Meyer-Olkin from factor analysis (0.566). It indicates that the samples were enough to conduct the survey. Next, the determination of relationship between the factors and the implementation of MSPO was analysed through Pearson’s Correlation analysis. From this analysis, it can be observed that the training and guidance factor has the significant relationship towards the implementation of MSPO compared to perceived benefit, knowledge, and financial factor. The most dominant factor that influences the implementation of MSPO was identified through multiple regression analysis and it can be observed that the training and guidance factor was the most dominant factor (beta value=0.298) compared to perceived benefit, knowledge, and financial factor. As a conclusion, government should plays a major role in providing training and guidance towards the smallholders in order to increase the implementation of MSPO and thus increasing their awareness towards the sustainability of oil palm.